2014
DOI: 10.1002/oby.20918
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mononuclear cells as a potential source of biomarkers to test the efficacy of weight‐loss strategies

Abstract: B arbara Reyn es, Rub en D ıaz-R ua, Margalida Cifre, Paula Oliver, and Andreu Palou Objectives: Peripheral blood mononuclear cells (PBMC) constitute an easily obtainable blood cell fraction useful in nutrition and obesity studies. Our aim was to study the potential use of PBMC to reflect metabolic recovery associated with weight loss in rats. Methods: By real-time PCR, the fasting response of key energy homeostatic genes in PBMC samples of control and cafeteria-obese rats and of rats fed a control diet after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 13 publications
6
37
0
1
Order By: Relevance
“…metabolic disorders (including obesity and diabetes) cardiovascular, endocrine disruption, and cancers, in accord with results observed in epidemiological settings (Langer et al, 2014; Arrebola et al, 2014; Recio-Vega et al, 2013; Lee et al, 2014; Wadzinski et al, 2014; Pereira-Fernandes et al, 2014; Sexton et al, 2013, Casas et al, 2014). Research utilizing PBMC cells in human are now being widely used to test for the efficacy of new drugs and treatments, to divulge the differential gene expression patterns induced by toxicity, and to study downstream effectors, all of which can be used as a potential source for developing disease-specific biomarkers (Reynes et al, 2014; Saidijam et al, 2014; Roccaet et al, 2014; Kong 2014). In such a model, studying the gene expression changes might provide us a valuable insights and better understanding of their mechanism(s) of action by highlighting which enzymes or proteins are targeted by these exposures.…”
Section: Discussionmentioning
confidence: 99%
“…metabolic disorders (including obesity and diabetes) cardiovascular, endocrine disruption, and cancers, in accord with results observed in epidemiological settings (Langer et al, 2014; Arrebola et al, 2014; Recio-Vega et al, 2013; Lee et al, 2014; Wadzinski et al, 2014; Pereira-Fernandes et al, 2014; Sexton et al, 2013, Casas et al, 2014). Research utilizing PBMC cells in human are now being widely used to test for the efficacy of new drugs and treatments, to divulge the differential gene expression patterns induced by toxicity, and to study downstream effectors, all of which can be used as a potential source for developing disease-specific biomarkers (Reynes et al, 2014; Saidijam et al, 2014; Roccaet et al, 2014; Kong 2014). In such a model, studying the gene expression changes might provide us a valuable insights and better understanding of their mechanism(s) of action by highlighting which enzymes or proteins are targeted by these exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs), composed of cells, including lymphocytes, monocytes, and dendritic cells, can be easily obtained from blood and have been used as a tool in nutrition studies [9] and as a common target of immunological studies in animals and humans [10]. In addition, the transcriptome or gene expression analysis in PBMCs can reveal information on the lipid metabolism in obesity-associated organs, adipose tissue, and the liver [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among accessible samples, blood cells are increasingly being investigated as a source of transcript-based biomarkers in nutritional and obesity studies. It has been shown that gene expression in blood cells can mirror gene expression changes in key tissues in energy homeostasis and respond to both internal and external stimuli (Reynes et al 2015;Oliver et al 2013;de Mello et al 2012). …”
Section: Introductionmentioning
confidence: 99%